Happy taxpayers? Income taxation and well-being - Alpaslan Akay; Olivier Bargain; Mathias Dolls; Dirk Neumann; Andreas Peichl; Sebastian Siegloch (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper offers a first empirical investigation of how labor taxation (income and payroll taxes) affects individuals' well-being. For identification, we exploit exogenous variation in tax rules over time and across demographic groups using 26 years of German panel data. We find that the tax effect on subjective well-being is significant and positive when controlling for income net of taxes. This interesting result is robust to numerous specification checks. It is consistent with several possible channels through which taxes affect welfare including public goods, insurance, redistributive taste and tax morale.
Keywords: H21; H41; I38; 330; subjective well-being; taxation; public goods